Faktor Determinan dan Kejadian Hipertensi pada Usia Produktif di Ciputat, Tangerang Selatan - Devi Syafira; Thresya Febrianti (Ikatan Ahli Kesehatan Masyarakat Indonesia Kota Tangerang Selatan, 2021)
Based on the Banten Provincial Health Office, (2016) Hypertension still ranks the highest of all non-communicable diseases reported at 24.68. The prevalence of hypertension in the productive age in 2019 in the work area of the Ciputat Health Center is 20%. So that hypertension becomes a disease problem by placing 3rd in the Ciputat Health Center. The object of this study is conducted to determine description of the factors associated with the incidence of hypertension in productive age in the work area of the Ciputat Health Center in 2019. Methods: The study design used was cross-sectional with secondary data for December 2019 SIPTM Surveillance. A sample of 163 people was taken using simple random sampling technique. Data analysis used chi square test (Î± = 0.05). Results: Variables related to the incidence of hypertension in productive age are family history (p. value = 0.000, PR = 1,8), age (p.value = 0.012, PR = 1,4), consumption of fruits and vegetables (p.value = 0.004, PR= 1,52, physical activity (P.value= 0.004, PR= 1,62), smoking habit (p.value= 0.004, PR=1,69) while the unrelated variable is alcohol consumption (P. value = 0.114, PR = 3.8), gender (P. value = 0.453, PR = 1.4 ), Overweight (P.value= 0,533, PR= 1.1 AR=0,47%). Conclusion: Risk factors of hypertension are family history, age, lack of fruit and vegetable consumption, physical activity and smoking habits. Suggestion: Education is needed to the working area community at the Ciputat Health Center such as counseling activities for risk factors related to the incidence of hypertension.